Simultaneous Inhibition of EGFR and HER2 via Afatinib Augments the Radiosensitivity of Nasopharyngeal Carcinoma Cells - Huang, Fangling (J Cancer, 2019)
Ionizing radiation (IR) is the central component of the therapeutic scheme for nasopharyngeal carcinoma (NPC) at present. Previous studies show that inhibition of epidermal growth factor receptor (EGFR) enhances the radiosensitivity of NPC; however the effects of EGFR-targeted agents are limited. In this study, we observed that simultaneously inhibition of EGFR and HER2 by afatinib could augment the radiosensitivity of NPC cells; this approach has an advantage over erlotinib-mediated inhibition of EGFR alone. The afatinib-induced augmentation of NPC cell radiosensitivity was associated with increases in apoptosis and accumulation of DNA damage that were induced by radiation. In addition, the crosstalk between radiation-induced activities and EGFR-, and HER2-related downstream pathways may contribute to the enhancement of radiosensitivity. Our findings indicate the potential of repositioning afatinib or other ERBB-family-targeted agents for improving radiation response in NPC cells.